Physical and Mechanical Properties of Samama Wood (Antocephalus macropylus Roxb.) Grown in Mollucas Island - Tekat D Cahyono; Syarif Ohorella; Fauzi Febrianto (Masyarakat Peneliti Kayu Indonesia, 2012)
People are less interest to the fast growing species since the quality is inferior compared to commercial wood. A research has been done to identify the physical and mechanical properties of samama wood (Antocephalus macrophylus (Roxb.)) from Mollucas island. Eight years old samama wood with diameter of 30 - 45 cm and height of 8 – 11 meter were used as samples. The parameters measured were moisture content (MC), specific gravity (SG), tangential and radial shrinkages, bending strength (MOR and MOE), tension and compression strengths parallel to grain and hardness. The result showed that the MC of samama wood decreased from bottom to upper and from outer to inner parts, while SG decreased from bottom to upper and from inner to outer part. Tangential and radial shrinkages of samama wood were much affected by vertical position. The MOE and MOR of samama wood decreased from bottom to upper part, while tension and compression strengths parallel to grain direction decreased form inner to outer part. On the other hand, hardness of samama wood decreased from bottom to upper and from inner to outer parts. Based on PKK NI5-1961 classification, samama wood belonged to strength class of III and IV.Key words: mechanical properties, Mollucas Island, physical properties, samama wood